PENERAPAN STUDY VISIT UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA DALAM MENGEMBANGKAN TEKNOLOGI TEPAT GUNA BIDANG PENDIDIKAN - Parmin, Parmin; Widiyatmoko, Arif (Universitas Negeri Semarang, 2011)
The teamâ€™s findings pengampu lecturer in learning suggests that students when given an assignment to create / modify props / lab science experience difficulties. Most students collect assignments product is not the work itself or the group, but the Internet search results. From the assessment results of the assignment, less than 30% of students who scored â‰¥ 75 so that if no immediate action is taken, the course learning objectives IPA Professional Development Teacher is not reached. Research purposes to improve the ability of students in developing appropriate technology fields Science Education. The study was conducted in a class action Prodi Science Education with the goal of student rombel 2, which amounted to 25 people. Results showed students have been able to create or modify props / lab science well, evidenced from the appraisal report containing a draft study visit product design with a range of scores obtained between 82 to 91 and from assessments of products that have made students more than 70% have earned a good category. The conclusions of this research is the ability of students in developing appropriate technology education can be improved through the implementation of study visit.